2014
DOI: 10.1007/s00436-014-4121-4
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal properties of the formulations based on essential oils from Cymbopogon winterianus and Syzygium aromaticum plants

Abstract: The cattle tick, Rhipicephalus (Boophilus) microplus, has caused serious harm to livestock raising in Brazil, considering the costs of controlling it, loss of revenue due to smaller production of milk and meat, and damage to leather, in addition to transmitting diseases. The use of medicinal plants is considered an alternative to the recurring resistance to chemicals. Due to the need for efficient alternatives with less environmental impact, this study aimed to develop contact formulations with essential oils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…The relative percentages of components were calculated based on the total quantity of the four major components because other compounds were also present, although not in significant proportions. Despite all the factors that may interfere in the chemical composition of an essential oil, the present results corroborate the findings of other research studies carried out on clove essential oil that showed the major constituent in this oil to be eugenol (Silvestri et al ., ; Mello et al ., ; Jairoce et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The relative percentages of components were calculated based on the total quantity of the four major components because other compounds were also present, although not in significant proportions. Despite all the factors that may interfere in the chemical composition of an essential oil, the present results corroborate the findings of other research studies carried out on clove essential oil that showed the major constituent in this oil to be eugenol (Silvestri et al ., ; Mello et al ., ; Jairoce et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, the need for safer products that are less harmful to both man and the environment, combined with a growing interest in organic farming practices, has led to an increase in research into the development of alternative approaches to ectoparasite management, amongst which botanical alternatives, such as essential oils, are currently receiving particular attention (Alves et al ., ; Ellse & Wall, ). Cymbopogon winterianus , Syzigium aromaticum , Lippia graveolens , Rosmarinus officinalis , Allium sativum and other essential oils, and isolated terpenoids (eugenol, thymol, carvacrol) have shown activity against cattle ticks (Martinez‐Velazquez et al ., ; Mello et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The acaricidal efficacy of different plant extracts against different developmental stages of hard ticks have been reported by many acarologists from 1985 to 2014 (e.g. Van Puyvelde et al, 1985;Panella et al, 1997;Al-Rajhy et al, 2003;Pereira and Famadas, 2006;Bagavan et al, 2009;Ravindran et al, 2011;de Mello et al, 2014).…”
Section: Discussionmentioning
confidence: 99%